A acenaphtho[1,2-b]benzo[f]quinoxaline derivative and electroluminescent device thereof

CN122940706APending Publication Date: 2026-10-20西安欧得光电材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611137713.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0006]为了克服上述现有技术的缺点,本发明的目的在于提供一种苊并[1,2-b]苯并[f]喹喔啉衍生物及其电致发光器件,用以解决现有的TADF材料寿命短、发光效率低、发光色纯度低等技术问题

Benefits of technology

本发明苊并[1,2-b]苯并[f]喹喔啉衍生物以刚性稠环为主体结构,将双氮杂环嵌入长程共轭骨架,LUMO电子云可沿完整稠环均匀离域,电子传输性能优异,可实现空穴、电子双极均衡传输,激子生成效率高;激子被束缚于分子骨架中部,分子间轨道重叠弱,大幅抑制三线态湮灭等非辐射损耗,主体向发光客体能量传递效率高;负电荷均匀分散在双氮共轭环上,单键电荷密度低,电化学稳定性更强,同时电荷复合均匀无局部发热,有效延缓基于该材料的薄膜老化,显著提升其对应器件发光效率与工作寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention belongs to the field of organic light-emitting materials and semiconductor technology, and provides an acenaphthene[1,2-b]benzo[f]quinoxaline derivative and its electroluminescent device. The acenaphthene[1,2-b]benzo[f]quinoxaline derivative has the following structural formula: It embeds a dinitrogen heterocycle into a long-range conjugated framework, allowing the LUMO electron cloud to be uniformly delocalized along the complete fused ring, resulting in excellent electron transport performance and achieving balanced bipolar transport of holes and electrons, with high exciton generation efficiency. Excitons are bound in the middle of the molecular framework, with weak intermolecular orbital overlap, significantly suppressing non-radiative losses such as triplet annihilation, and resulting in high energy transfer efficiency from the host to the luminescent guest. Negative charges are uniformly dispersed on the dinitrogen conjugated ring, with low single-bond charge density and stronger electrochemical stability. Simultaneously, uniform charge recombination without localized heating effectively delays the aging of films based on this material, significantly improving the luminous efficiency and lifespan of the corresponding devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic light-emitting materials and semiconductor technology, specifically relating to an acenaphthene[1,2-b]benzo[f]quinoxaline derivative and its electroluminescent device. Background Technology

[0002] New materials are the core driving force for innovation in display technology, and their development has always been one of the key tasks of scientific research in the display field.

[0003] In recent years, organic light-emitting diodes (OLEDs) have become a hot research topic in the lighting and display fields due to their excellent characteristics such as self-illumination, high brightness, high contrast, transparency, wearability, foldability, low power consumption, wide viewing angle, and low temperature resistance. With the development of technology, researchers have developed the third-generation light-emitting material for OLEDs—thermally activated delayed fluorescence (TADF) material. TADF material has a small singlet-triplet energy level difference (ΔEst), and triplet excitons can effectively convert triplet excitons to singlet excitons through the anti-system crossing (RISC) process, achieving an internal quantum efficiency of nearly 100%. Therefore, TADF material has attracted much attention as an emerging material for OLED devices.

[0004] Typically, organic TADF materials utilize a D (donor)-A (accept) configuration to reduce overlap between HOMO and LUMO, thereby minimizing ΔEst. However, the intramolecular charge transfer (ICT) property of TADF materials easily leads to structural relaxation in the excited state, exhibiting a large Stokes shift, broad emission spectrum, and large full width at half maximum (FWHM). This results in electroluminescent devices fabricated from TADF materials still facing problems such as low luminous efficiency, short lifetime, and low emission color purity.

[0005] Therefore, developing a new type of TADF material with long lifespan, high efficiency, and narrow half-peak width remains a major task for researchers. Summary of the Invention

[0006] In order to overcome the shortcomings of the prior art, the present invention aims to provide an acenaphthene[1,2-b]benzo[f]quinoxaline derivative and its electroluminescent device to solve the technical problems of short lifespan, low luminous efficiency and low luminous color purity of existing TADF materials.

[0007] This invention is achieved through the following technical solution: In a first aspect, the present invention provides an acenaphthene[1,2-b]benzo[f]quinoxaline derivative having the structural formula shown in Formula I:

[0008] Formula I In Formula I: R1, R2, R3, and R4 are independently selected from H, C1-C6 alkyl groups, and cyano groups, respectively. R1, R2, R3, and R4 cannot all be H. R5 is selected from substituted or unsubstituted C6~C. 20 aryl, substituted or unsubstituted C6~C 20 heteroaryl, substituted or unsubstituted C6~C 30 Aromatic secondary amine group.

[0009] Preferably, R2 and R3 are both methyl groups, and R2 and R3 are either bonded to each other or independent of each other.

[0010] Preferably, when the aryl, heteroaryl, or aromatic secondary amine group is substituted by a substituent, the substituent is selected from: methyl, isopropyl, tert-butyl, D, F, deuterated tert-butyl, cyano, and phenyl.

[0011] Preferably, the heteroatoms in the heteroaryl group are: N, O, S, Si, or Ge.

[0012] Preferably, R5 is selected from the following groups:

[0013] In groups Q1~Q71, " "Indicates R5 and the main structure" The bonding positions.

[0014] Preferably, the acenaphthene[1,2-b]benzo[f]quinoxaline derivative is selected from the following compounds: .

[0015] A second aspect of the present invention provides an electroluminescent device comprising a cathode layer, an anode layer, and an organic layer located between the cathode layer and the anode layer, the organic layer comprising a hole transport layer, a light-emitting layer, and an electron transport layer, the hole transport layer being located between the anode layer and the light-emitting layer, and the electron transport layer being located between the cathode layer and the light-emitting layer; the light-emitting layer comprises a acenaphthene[1,2-b]benzo[f]quinoxaline derivative as described above.

[0016] Preferably, the components of the light-emitting layer include a host light-emitting material and a guest light-emitting material; the host light-emitting material is selected from one of the following compounds: , ,

[0017] The guest luminescent material comprises the acenaphthene[1,2-b]benzo[f]quinoxaline derivative as described above.

[0018] Furthermore, the mass ratio of the main luminescent material to the guest luminescent material is (97~99):(1~3).

[0019] In a specific embodiment of the present invention, the organic electroluminescent device comprises, in sequence from the anode layer to the cathode layer, a substrate, an anode layer, a hole injection layer (HIL), a hole transport layer, an electron blocking layer (EBL), an emission material layer (EML), a hole blocking layer (HBL), an electron transport layer, an electron injection layer (EIL), a cathode layer, and a high refractive index covering protection layer (CPL).

[0020] As a substrate, it needs to have high mechanical strength, excellent thermal stability, excellent water resistance and excellent transparency; polyethylene terephthalate (PET) plastic is preferred.

[0021] As the anode layer, the anode layer material is preferably a material with a high work function in order to facilitate the injection of holes into the organic layer. Specific examples of anode layer materials that can be used in this invention include: metals such as vanadium, chromium, copper, zinc, and gold, or their alloys; oxides such as zinc oxide, aluminum oxide, or tin dioxide; and conductive polymers such as polypyrrole and polyaniline.

[0022] The compounds used in the organic layers other than the light-emitting layer in this invention can be small organic molecules, large organic molecules, polymers, and combinations thereof. The materials used for the hole injection layer, hole transport layer, electron blocking layer, electron transport layer, and electron injection layer are selected from industry-leading cost-effective materials. The compatibility between the layers needs to be determined through a series of tests and screening processes.

[0023] Preferably, the material of the hole injection layer in this invention is MoO3.

[0024] Preferably, the material of the hole transport layer in this invention is selected from one of the following materials:

[0025] .

[0026] Preferably, the material of the electron blocking layer in this invention is selected from one of the following materials: .

[0027] Preferably, the material of the hole-blocking layer in this invention is selected from one of the following materials: .

[0028] Preferably, the material of the electron transport layer in this invention is selected from one of the following materials: .

[0029] Preferably, the material of the electron injection layer in this invention is LiF.

[0030] As a cathode layer, the cathode layer material is preferably a material with a low work function in order to facilitate the injection of electrons into the functional organic layer. Specific examples of cathode layer materials that can be used in this invention include: metals or alloys thereof such as magnesium, calcium, sodium, potassium, titanium, indium, yttrium, lithium, gadolinium, aluminum, silver, tin, and lead, for example Mg-Al and Mg-Ag.

[0031] As a high-refractive-index capping layer, it can improve the refractive index of the cathode layer surface and increase the light extraction efficiency; the preferred material for the capping layer is... .

[0032] A third aspect of the present invention provides a method for fabricating the above-described electroluminescent device. In a specific embodiment, the fabrication method is as follows: an anode layer is adhered to a substrate after pretreatment and cleaning; then, a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, a hole blocking layer, an electron transport layer, and an electron injection layer of predetermined thickness are sequentially vapor-deposited under low-temperature conditions; a cathode layer and a high-refractive-index capping layer are sputtered under low-temperature conditions; and finally, the device is packaged using conventional device packaging methods to obtain the electroluminescent device.

[0033] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides acenaphthene[1,2-b]benzo[f]quinoxaline derivatives with rigid fused rings. With a bis(nitrogen) heterocycle embedded in a long-range conjugated framework as the main structure, the LUMO electron cloud can be uniformly delocalized along the complete fused ring, resulting in excellent electron transport performance and enabling balanced bipolar transport of holes and electrons, leading to high exciton generation efficiency. Excitons are bound in the middle of the molecular framework, with weak intermolecular orbital overlap, significantly suppressing non-radiative losses such as triplet annihilation, and resulting in high energy transfer efficiency from the host to the luminescent guest. Negative charges are uniformly dispersed on the bis(nitrogen) conjugated ring, with low single-bond charge density, resulting in stronger electrochemical stability. At the same time, uniform charge recombination without localized heating effectively delays the aging of films based on this material, significantly improving the luminescence efficiency and operating life of corresponding devices.

[0034] The electroluminescent device provided by this invention uses acenaphthene[1,2-b]benzo[f]quinoxaline derivative as the guest light-emitting material, which effectively improves the luminous efficiency, extends the service life, and greatly improves the purity of the emitted color. The light emitted by the electroluminescent device is in the range of green to red light. Attached Figure Description

[0035] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0036] Figure 1 This is a cross-sectional view of the electroluminescent device of the present invention; Figure 2 The NMR spectrum of compound 1 (compound preparation example 1) of the present invention; Figure 3 The NMR spectrum of compound 35 (compound preparation example 2) of the present invention; Figure 4 The NMR spectrum of compound 79 (compound preparation example 3) of the present invention; Figure 5 The NMR spectrum of compound 83 (compound preparation example 4) of the present invention; Figure 6 The NMR spectrum of compound 86 (compound preparation example 5) of the present invention; Figure 7 The NMR spectrum of compound 90 (compound preparation example 6) of the present invention; Figure 8 The NMR spectrum of compound 93 (compound preparation example 7) of the present invention. Detailed Implementation

[0037] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention.

[0038] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. Process equipment or apparatus not specifically specified in the following examples are all conventional equipment or apparatus in the art. All raw materials used in the following examples are conventional commercially available products with specifications in the art, unless otherwise stated.

[0039] The key reactants involved in this invention include: .

[0040] Compound preparation example 1 (synthesis of compound 1):

[0041] Step 1: Add reactant p1 (18.2 g, 0.1 mol) and 200 mL of acetic acid to a 500 mL three-necked flask. Add 6-bromonaphthalene-1,2-diamine (23.7 g, 0.1 mol), start stirring, and reflux the system at 120 °C for 12 h. After the reaction is complete, concentrate under reduced pressure to remove the acetic acid solvent. Add 200 mL of ethyl acetate and 200 mL of water, and stir for 10 minutes. Separate the liquid and dry the organic phase with anhydrous sodium sulfate, then concentrate under reduced pressure to obtain the residue. Recrystallize the residue from ethyl acetate / petroleum ether (3:1) to obtain intermediate M1, weighing 33.5 g, with a yield of 87.5% and a purity of 97% according to HPLC (High Performance Liquid Chromatography).

[0042] Step 2: Under nitrogen protection, add intermediate M1 (3.8 g, 0.01 mol), reactant q1 (3.2 g, 0.01 mol), and 25 mL of toluene to a 50 mL three-necked flask. Stir until the solution is clear, then add Pd2(dba)3 (0.18 g, 0.2 mmol), [(4-(N,N-dimethylamino)phenyl]di-tert-butylphosphine (Am-phos) (0.11 g, 0.4 mmol), and sodium tert-butoxide (1.9 g, 0.02 mol). The reaction solution was heated to 110℃ and reacted for 10 hours. After the reaction was complete, the mixture was filtered hot using diatomaceous earth. The filtrate was cooled to room temperature, washed with purified water, and separated. The organic phase was retained, and the aqueous phase was extracted with ethyl acetate. The organic phases were combined, dried over anhydrous magnesium sulfate, concentrated, and column filtered (petroleum ether:ethyl acetate = 8:1) to obtain compound 1, weighing 5.1 g, with a yield of 81.8%, HPLC purity of 99%, and LC-MS showing a molecular weight of 621.7. The NMR spectrum of compound 1 is shown below. Figure 2 As shown.

[0043] 1H NMR data for compound 1: 1H NMR (500 MHz, CD3OD) δ 8.55 (s, 1H), 8.32 (s, 1H), 7.96 (t, 1H). J = 12.6 Hz, 3H), 7.84 – 7.72 (m, 5H), 7.68 (d, J = 10.0 Hz,3H), 7.59 – 7.45 (m, 5H), 7.39 (d, J = 25.0 Hz, 3H), 7.22 – 7.06 (m, 6H).

[0044] Compound preparation example 2 (synthesis of compound 35):

[0045] Step 1: The synthesis process of compound 35 is similar to the synthesis process of intermediate M1 to compound 1, using reactant q. 35 (2.8 g, 0.01 mol) replaced reactant q1 (3.2 g, 0.01 mol) to give compound 35, weighing 4.9 g, with a yield of 84.1%, HPLC purity of 99%, and LC-MS showing a molecular weight of 583.8. The NMR spectrum of compound 35 is shown below. Figure 3 As shown.

[0046] 1H NMR data for compound 35: 1H 583.8 NMR (500 MHz, CD3OD) δ 7.98 (s, 1H), 7.80 (s, 2H), 7.68 (d, 2H) J = 10.0 Hz, 3H), 7.55 (d, J = 5.0 Hz, 3H), 7.17 (s, 1H), 7.11 (d, J = 5.0 Hz, 9H), 1.33 (s, 18H).

[0047] Compound preparation example 3 (synthesis of compound 79):

[0048] Step 1: The synthesis process of intermediate M2 is the same as that of reactant p1 to intermediate M1. Reactant p1 (18.2g, 0.1mol) is replaced with reactant p2 (21.0g, 0.1mol) to obtain intermediate M2, weighing 34.6g, with a yield of 84.2% and an HPLC purity of 97%.

[0049] Step 2: Under nitrogen protection, add intermediate M2 (4.1g, 0.01mol) and reactant q to a 50mL three-necked flask. 51The following solutions were prepared: 2.3 g (0.01 mol), Pd(PPh3)4 (0.23 g, 0.2 mmol), K2CO3 (2.8 g, 0.02 mol), 20 mL of tetrahydrofuran, and 5 mL of H2O. The mixture was stirred and refluxed for 15 h until the reaction was complete. The reaction solution was washed with water and separated. The organic phase was passed through a diatomaceous earth funnel, and the filtrate was collected. The filtrate was concentrated under reduced pressure to obtain the residue, which was then purified by silica gel column chromatography. The solvents used were petroleum ether and ethyl acetate in a volume ratio of 3:1, yielding compound 79, weighing 4.3 g, with a yield of 82.5%, an HPLC purity of 99%, and a molecular weight of 520.7 as shown by LC-MS. The NMR spectrum of compound 79 is shown below. Figure 4 As shown.

[0050] 1H NMR data for compound 79: 1 H NMR (500 MHz, CD3OD) δ 8.02 (d, J = 16.8 Hz, 2H), 7.68 (t, J = 5.5 Hz, 3H), 7.61 (s, 1H), 7.55 (s, 1H), 7.39 (d, J = 10.0 Hz, 3H), 7.31 (s, 1H), 7.18 (s, 1H), 2.78 (s, 6H), 1.35 (s, 9H), 1.28 (s, 9H).

[0051] Compound preparation example 4 (synthesis of compound 83):

[0052] Step 1: The synthesis process of intermediate M3 is the same as that of reactant p1 to intermediate M1. Reactant p1 (18.2g, 0.1mol) is replaced with reactant p3 (21.0g, 0.1mol) to obtain intermediate M3, weighing 35.4g, with a yield of 86.1% and an HPLC purity of 96%.

[0053] Step 2: The synthesis process of compound 83 is the same as that of intermediate M2 to compound 79. Intermediate M2 (4.1 g, 0.01 mol) is replaced with intermediate M3 (4.1 g, 0.01 mol), and reactant q is used... 52 (2.3g, 0.01mol) Replace reactant q 51 (2.3 g, 0.01 mol) yielded compound 83, weighing 4.4 g, with a yield of 84.3%, HPLC purity of 99%, and LC-MS showing a molecular weight of 520.7. The NMR spectrum of compound 83 is shown below. Figure 5 As shown.

[0054] 1H NMR data for compound 83: 1 H NMR (500 MHz, Chloroform) δ 8.03 (d, J =10.3 Hz, 2H), 7.73 (s, 2H), 7.65 (d, J = 20.0 Hz, 3H), 7.59 – 7.51 (m, 4H), 7.38 (s, 1H), 2.97 (s, 6H), 1.32 (s, 18H).

[0055] Compound preparation example 5 (synthesis of compound 86):

[0056] Step 1: The synthesis process of intermediate M4 is the same as that of intermediate M1 from p1. Reactant p1 (18.2g, 0.1mol) is replaced with reactant p4 (29.4g, 0.1mol) to obtain intermediate M4, weighing 40.6g, with a yield of 81.9% and an HPLC purity of 97%.

[0057] Step 2: The synthesis of compound 86 follows the same process as the synthesis of intermediates M2 to 79, replacing intermediate M2 (4.1 g, 0.01 mol) with intermediate M4 (5.0 g, 0.01 mol), and using reactant q... 58 (2.8 g, 0.01 mol) Replace reactant q 51 (2.3 g, 0.01 mol) yielded compound 86, weighing 5.4 g, with a yield of 82.5%, HPLC purity of 99%, and LC-MS showing a molecular weight of 648.9. The NMR spectrum of compound 86 is shown below. Figure 6 As shown.

[0058] 1H NMR data for compound 86: 1 H NMR (500 MHz, Chloroform) δ 8.20 (d, J =15.0 Hz, 4H), 8.04 (d, J = 4.9 Hz, 2H), 7.69 (dd, J = 10.5, 4.5 Hz, 5H), 7.55 (s,1H), 7.47 (d, J = 5.0 Hz, 4H), 7.38 (s, 1H), 1.48 (s, 27H).

[0059] Compound Preparation Example 6 (Synthesis of Compound 90):

[0060] Step 1: The synthesis process of intermediate M5 is the same as that of reactant p1 to intermediate M1. Reactant p1 (18.2g, 0.1mol) is replaced with reactant p5 (20.8g, 0.1mol) to obtain intermediate M5, weighing 34.1g, with a yield of 83.4% and an HPLC purity of 96%.

[0061] Step 2: The synthesis process of compound 90 is the same as that of intermediate M2 to compound 79. Intermediate M2 (4.1g, 0.01mol) is replaced with intermediate M5 (4.1g, 0.01mol), and reactant q is used... 53 (2.3g, 0.01mol) Replace reactant q 51 (2.3 g, 0.01 mol) yielded compound 90, weighing 4.2 g, with a yield of 80.8%, HPLC purity of 99%, and LC-MS showing a molecular weight of 518.7. The NMR spectrum of compound 90 is shown below. Figure 7 As shown.

[0062] 1H NMR data for compound 90: 1 H NMR (500 MHz, Chloroform) δ 8.03 (d, J =10.1 Hz, 2H), 7.90 – 7.82 (m, 3H), 7.68 (d, J = 15.0 Hz, 3H), 7.51 (d, J = 35.0Hz, 2H), 7.38 (s, 1H), 7.26 (s, 1H), 3.52 (s, 4H), 1.35 (s, 18H).

[0063] Compound preparation example 7 (synthesis of compound 93):

[0064] Step 1: The synthesis process of intermediate M6 is the same as that of reactant p1 to intermediate M1. Reactant p1 (18.2g, 0.1mol) is replaced with reactant p6 (23.2g, 0.1mol) to obtain intermediate M6, weighing 33.7g, with a yield of 77.8% and an HPLC purity of 96%.

[0065] Step 2: The synthesis process of compound 93 is the same as that of intermediate M2 to compound 79. Intermediate M2 (4.1 g, 0.01 mol) is replaced with intermediate M6 (4.3 g, 0.01 mol), and intermediate reactant q is used. 53 (2.3g, 0.01mol) Replace reactant q51 (2.3 g, 0.01 mol) yielded compound 93, weighing 4.2 g, with a yield of 76.5%, an HPLC purity of 99%, and an LC-MS molecular weight of 542.7. The NMR spectrum of compound 93 is shown below. Figure 8 As shown.

[0066] 1H NMR data for compound 93: 1 H NMR (500 MHz, Chloroform) δ 8.03 (d, J =10.1 Hz, 2H), 7.90 – 7.82 (m, 3H), 7.68 (d, J = 15.0 Hz, 3H), 7.51 (d, J = 35.0Hz, 2H), 7.38 (s, 1H), 7.26 (s, 1H), 3.52 (s, 4H), 1.35 (s, 18H).

[0067] The synthesis of other compounds followed the synthesis procedures of compounds 1, 35, 79, 83, 86, 90, and 93, respectively, with the appropriate starting reactants q (q1~q2) selected during the synthesis. 78 ), reactants p (p1~p6). The reactant compositions of some compounds in this invention are shown in Table 1: Table 1. Reactant composition of some compounds in this invention

[0068] The electroluminescent devices of Examples 1-83 and Comparative Examples 1-3 are prepared below.

[0069] Schematic diagrams of the electroluminescent devices in the various embodiments and comparative examples of this invention are shown below. Figure 1 As shown, it includes a substrate 1, an anode layer 2, a hole injection layer 3, a hole transport layer 4, an electron blocking layer 5, a light-emitting layer 6, a hole blocking layer 7, an electron transport layer 8, an electron injection layer 9, a cathode layer 10, and a capping layer 11.

[0070] Example 1 (Electroluminescent device containing compound 1) An electroluminescent device containing compound 1, comprising, from the anode layer to the cathode layer, PET plastic, indium tin oxide (ITO) material, MoO3, HT-1, EB-1, a light-emitting layer, HB-1, ET-1, LiF, Al-Mg (Al:Mg=8:2), and CPL; the CPL is made of the following material: ; In the light-emitting layer, the following is used Compound 1 was used as the guest luminescent material, with a mass ratio of PH-2 to compound 1 of 98:2.

[0071] The method for preparing the electroluminescent device containing compound 1 includes the following steps: 1. Using 1.5mm thick PET plastic as substrate 1 and 0.15μm thick ITO material as anode layer 2, the substrate is washed in sequence by alkaline washing, pure water washing, drying, and ultraviolet-ozone washing to remove organic residues on the surface of PET plastic and ITO material.

[0072] 2. A layer of ITO material is adhered to PET plastic. Using a vacuum evaporation device, a 20nm thick MoO3 film is deposited as a hole injection layer 3. Then, a 45nm thick HT-1 film is deposited as a hole transport layer 4. Subsequently, a 30nm thick EB-1 film is deposited as an electron blocking layer 5. On the EB-1, a 60nm thick light-emitting layer 6 formed by PH-2 and compound 1 with a mass ratio of 98:2 is deposited. On the light-emitting layer 6, a 10nm thick compound HB-1 film is deposited as a hole blocking layer 7. Then, a 30nm thick ET-1 film is deposited as an electron transport layer 8. On the electron transport layer 8, a 16nm thick LiF film is deposited as an electron injection layer 9. After the electron injection layer 9 is deposited, a 20nm thick Al-Mg (Al:Mg=8:2) alloy is sputtered as a cathode layer 10 using a low-temperature sputtering method. Finally, a 40nm thick CPL film is deposited on the cathode layer 10 as a high refractive index capping layer 11.

[0073] 3. Vacuum encapsulation of MoO3, HT-1, EB-1, light-emitting layer 6, HB-1, ET-1 and LiF layer to obtain an electroluminescent device.

[0074] Examples 2-83 The difference from Example 1 is that in Examples 2 to 83, compounds 2 to 79, 83, 86, 90 and 93 were selected as guest luminescent materials in the luminescent layer 6, respectively.

[0075] Comparative Example 1 The difference from Example 1 is that, in the light-emitting layer 6, a method is used. As a guest luminescent material.

[0076] Comparative Example 2 The difference from Example 1 is that, in the light-emitting layer 6, a method is used. As a guest luminescent material.

[0077] Comparative Example 3 The difference from Example 1 is that, in the light-emitting layer 6, a method is used. As a guest luminescent material.

[0078] The electroluminescent devices from the above embodiments and comparative examples were fabricated into 30mm × 30mm samples. Then, under the same device fabrication process conditions, the anode and cathode layers were connected using an industry-known driving circuit. The luminous performance indicators of each electroluminescent device were tested. For the electroluminescent devices, at 10mA / cm... 2 The driving voltage and luminous efficiency were measured at a current density of 20 mA / cm². 2 The time required for the brightness to become 95% of its initial brightness at a given current density (LT) 95 (i.e., lifespan). The test results are shown in Table 2.

[0079] Table 2

[0080] Notes: 1. Comparative examples are abbreviated as "Pro.", and exemplary examples are abbreviated as "Ex."; 2. "EQE" in the table header refers to the value at 1000 cd / m³. 2 External quantum efficiency at operating brightness.

[0081] As can be seen from the performance data in Table 2, compared with the electroluminescent devices of Comparative Examples 1-3, the electroluminescent devices prepared using the acenaphthene[1,2-b]benzo[f]quinoxaline derivative of this invention as the guest luminescent material show a significant improvement in overall luminous efficiency, with a significant increase in external quantum efficiency and a lifespan extended by more than 2 times. This may be because the structure of the main structure of this invention, with its bis(ortho-n) pyrazine center, can regulate the global delocalization of the electron cloud, uniform charge dispersion, and exciton spatial confinement. This achieves both hole-electron bipolar balanced transport to improve luminous efficiency and reduces single-bond charge density and inhibits exciton annihilation, thereby reducing the electrochemical degradation of the organic layer from the root of molecular electronic structure, and simultaneously improving the device's luminous efficiency and operating life. In Comparative Example 2, the compound used as the guest luminescent material has a short conjugated chain and a narrow electron delocalization range, resulting in poor luminous efficiency and device lifespan. In Comparative Example 3, the main structure of the compound used as the guest luminescent material is acenaphthene-1,10-phenanthroline. The two electron-deficient nitrogen atoms in the molecule cause the LUMO electron cloud of the molecule to be delocalized at the edge of the molecule, resulting in weak electron transport capability, imbalance of charge carrier transport, and low exciton generation efficiency. Excitons are concentrated at the ends of the molecule, and there is a large overlap of intermolecular orbitals, which easily leads to non-radiative annihilation loss and poor energy transfer to the luminescent guest. The negative charge is concentrated on the CN bond, and the chemical bond is easily electrochemically broken. The superimposed local charge accumulation heats up and accelerates the aging of the thin film. In the end, the device has low luminous efficiency and short lifespan, and is not suitable as the host of the guest luminescent material.

[0082] As can be seen from the performance data in Table 2, compared with the electroluminescent devices of Comparative Examples 1 to 3, the half-width at half maximum (WHM) of the electroluminescent device in the embodiment of the present invention is significantly narrower, indicating that the electroluminescent device prepared by using acenaphthene[1,2-b]benzo[f]quinoxaline derivative as the guest luminescent material of the present invention emits light with higher color purity.

[0083] As can be seen from the performance data in Table 2, the light emitted by the electroluminescent device in this embodiment of the invention is in the range of green to red light. The wavelengths of Examples 9-11, 22-38, 40-42, 44, 45, 47-50, and 75-78 are in the red light range, possibly because the substituent R5 is a strong electron-donating group, such as: Q9-Q11 (indoline ring), Q22-Q38 (triarylamines, carbazoles), Q40-Q42 (benzidine), Q69-Q71 (phenoxazine / phenothiazine). When R5 is selected from this type of group, on the one hand, the HOMO energy level of the molecule is greatly raised through the conjugation electron-donating effect, and the HOMO-LUMO energy level difference is narrowed. According to the inverse relationship between photon energy and wavelength, the emission wavelength is red-shifted. On the other hand, this type of group itself has a large planar conjugated structure, which has a strong ability to bind its own electrons (i.e., HOMO orbitals), which can expand the delocalization range of the molecular π electrons, enhance the intramolecular DA charge transfer effect, further reduce the excited state transition energy, and finally make the emission spectrum of the compound stably fall in the red light range. In Example 83, when R2 and R3 are cyano-substituted, the emission wavelength of the device exhibits a red shift. This may be because cyano is a strong electron-withdrawing group, and its insertion into the R2 and R3 sites can significantly reduce the LUMO energy level of the molecule, narrow the HOMO-LUMO energy level difference, and enhance the intramolecular push-pull charge transfer effect, thereby reducing the transition energy and causing the emission wavelength of the compound to red shift. In Examples 80-82, when R2 and R3 are alkyl-substituted, the emission wavelength of the device exhibits a significant blue shift. This may be because the alkyl groups at the R2 and R3 sites are saturated sterically hindered weak electron-donating groups. Their steric hindrance distorts the conjugated plane of the molecule, compresses the π electron delocalization range, significantly increases the transition energy level difference, weakens the intramolecular charge transfer, and ultimately causes the emission wavelength of the compound to blue shift.

[0084] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of this invention.

Claims

1. A acenaphthene[1,2-b]benzo[f]quinoxaline derivative, characterized in that, Its structural formula is shown in Formula I: Formula I In Formula I: R1, R2, R3, and R4 are independently selected from H, C1-C6 alkyl groups, and cyano groups, and R1, R2, R3, and R4 cannot all be H. R5 is selected from substituted or unsubstituted C6~C. 20 aryl, substituted or unsubstituted C6~C 20 heteroaryl, substituted or unsubstituted C6~C 30 Aromatic secondary amine group.

2. The acenaphthene[1,2-b]benzo[f]quinoxaline derivative according to claim 1, characterized in that, R2 and R3 are both methyl groups, and R2 and R3 are either bonded to each other or independent of each other.

3. The acenaphthene[1,2-b]benzo[f]quinoxaline derivative according to claim 1, characterized in that, When the aryl, heteroaryl, or aromatic secondary amine group is substituted by a substituent, the substituent is selected from: methyl, isopropyl, tert-butyl, D, F, deuterated tert-butyl, cyano, and phenyl.

4. The acenaphthene[1,2-b]benzo[f]quinoxaline derivative according to claim 1, characterized in that, The heteroatoms in the heteroaryl group are selected from: N, O, S, Si, and Ge.

5. The acenaphthene[1,2-b]benzo[f]quinoxaline derivative according to claim 1, characterized in that, The R5 is selected from the following groups: In groups Q1~Q71, " "Indicates R5 and the main structure" The bonding positions.

6. The acenaphthene[1,2-b]benzo[f]quinoxaline derivative according to claim 1, characterized in that, The acenaphthene[1,2-b]benzo[f]quinoxaline derivatives mentioned above are selected from the following compounds: 。 7. An electroluminescent device, characterized in that, It includes a cathode layer, an anode layer, and an organic layer located between the cathode layer and the anode layer. The organic layer includes a hole transport layer, a light-emitting layer, and an electron transport layer. The hole transport layer is located between the anode layer and the light-emitting layer, and the electron transport layer is located between the cathode layer and the light-emitting layer. The light-emitting layer comprises the acenaphthene[1,2-b]benzo[f]quinoxaline derivative as described in any one of claims 1 to 6.

8. The electroluminescent device according to claim 7, characterized in that, The components of the light-emitting layer include a host light-emitting material and a guest light-emitting material; the guest light-emitting material comprises the acenaphthene[1,2-b]benzo[f]quinoxaline derivative as described in any one of claims 1 to 6.

9. The electroluminescent device according to claim 7, characterized in that, The host luminescent material is selected from one of the following compounds: 。 10. The electroluminescent device according to claim 7, characterized in that, The mass ratio of the main luminescent material to the guest luminescent material is (97~99):(1~3).